2017
DOI: 10.14429/dlsj.2.11108
|View full text |Cite
|
Sign up to set email alerts
|

Photon interaction parameters of different tissues of human organs

Abstract: <p>For proper planning in the radiography of different parts of human organs, knowledge of the photon interaction parameters in different tissues of human organs are essential. Studied the x-ray and gamma photon interaction parameters such as  linear attenuation coefficient, half value layer, tenth value layer, mean free path and effective electron density of almost all tissues of human organs [Adipose tissue,  Blood, Brain, Breast, Cell Nucleus, Eye Lens, GI tract, Heart, Kidney, Liver, Lung , Lymph, Mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The HVL values calculated by both methods increased as the photon energy increased for all anatomical structures. The HVL value for bone tissue of an x-ray photon with an energy of 0.1 MeV has been reported to be 1.94 cm [18]. Jarrah et al, in the study in which they compared the results obtained with the Monte Carlo simulation and the Geometric Progression fitting method, the HVL value for the breast tissue is approximately 30 cm [19].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The HVL values calculated by both methods increased as the photon energy increased for all anatomical structures. The HVL value for bone tissue of an x-ray photon with an energy of 0.1 MeV has been reported to be 1.94 cm [18]. Jarrah et al, in the study in which they compared the results obtained with the Monte Carlo simulation and the Geometric Progression fitting method, the HVL value for the breast tissue is approximately 30 cm [19].…”
Section: Resultsmentioning
confidence: 99%
“…When reviewing the literature, it is discovered that innovative methodologies for computing HVL values are presented, which may give answers for medical and industrial radiation applications [9,10,18,19]. A review of the literature indicated that there is presently no Monte Carlo-based sufficient tool for direct calculation of the HVL value and direct computation suitable for material design and all changes based on sophisticated simulation methods [9,20].…”
Section: Energymentioning
confidence: 99%